A 330 kb CENP-A binding domain and altered replication timing at a human neocentromere - Lo, Anthony W.I. (Oxford University Press, 2001)
Centromere protein A (CENP-A) is an essential centromere-specific histone H3 homologue. Using combined chromatin immunoprecipitation and DNA array analysis, we have defined a 330 kb CENP-A binding domain of a 10q25.3 neocentromere found on the human marker chromosome mardel(10). This domain is situated adjacent to the 80 kb region identified previously as the neocentromere site through lower-resolution immunofluorescence/FISH analysis of metaphase chromosomes. The 330 kb CENP-A binding domain shows a depletion of histone H3, providing evidence for the replacement of histone H3 by CENP-A within centromere-specific nucleosomes. The DNA within this domain has a high AT-content comparable to that of α-satellite, a high prevalence of LINEs and tandem repeats, and fewer SINEs and potential genes than the surrounding region. FISH analysis indicates that the normal 10q25.3 genomic region replicates around mid-S phase. Neocentromere formation is accompanied by a replication time lag around but not within the CENP-A binding region, with this lag being significantly more prominent to one side. The availability of fully sequenced genomic markers makes human neocentromeres a powerful model for dissecting the functional domains of complex higher eukaryotic centromeres.